Teaching With Data in the Social Sciences at Kansas State University: How Can K-State Libraries Support Undergraduate Instruction? - Bonella, Laura; Finch, Emily; Spahr, Kendra (Kansas State University Libraries, 2022)
K-State Libraries established a local research team to partner with Ithaka S+R on their multi-institutional study on teaching with data in the social sciences. The project was developed to gather information about how undergraduate instructors in the social sciences taught with and about quantitative data. The team hoped to establish baseline knowledge of faculty needs when teaching with data in order to inform our development of research data services. While this report focused on our institution, we hope the recommendations will be useful for librarians at other institutions as well. A previous version of this work had been made available in September 2021.
Keywords: Data; Social sciences; Academic libraries; Undergraduate instruction; Ithaka